Silk fibroin hard material, preparation method and application
通过气泡去除处理技术,解决了丝蛋白硬质材料中气泡残留的问题,提高了材料的力学性能和生产稳定性,实现了成本降低和大规模生产的目标。
Patent Information
- Application Number
- CN202411573940.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, silk protein hard materials prepared by methanol recrystallization method and hydrogel natural drying method have problems such as large amounts of bubbles remaining inside, high production costs, and difficulty in large-scale production of direct hot pressing molding.
The bubble removal treatment technology is used to remove bubbles in the regenerated silk fibroin solution or silk fibroin/gelatin composite solution through centrifugation, ultrasonication, vacuum, etc., to improve the purity and mechanical properties of the material.
Effectively remove bubbles in silk protein hard materials, improve the mechanical properties and process stability of the material, reduce production costs, and realize the possibility of large-scale production.
Smart Images

Figure CN119424769A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a silk fibroin hard material, a preparation method and an application thereof. Background Art
[0002] Silk fibroin can be applied to the bone nail and bone plate markets such as metaphyseal fractures in joints, bone graft fixation for artificial joint revision, ligament reconstruction for sports injuries, and bone block transplantation for defective parts of bone tumor resection. With the aging population in my country, the number of fracture patients is increasing, and the demand for bone nails and bone plates may continue to rise, and the industry development is relatively certain.
[0003] At present, the widely used degradable bone fixation materials are mainly high molecular polymers, including polyglycolic acid (PGA), polylactic acid (PLA) and polylactic acid-glycolic acid copolymer (PLGA). Over the years, with the continuous innovation and research of foreign researchers, high molecular degradable bone fixation materials have basically met clinical requirements, but PLA-type polymer materials still have shortcomings as orthopedic internal fixation materials, among which the biggest problem is the postoperative complications of PLA-type bone fixation materials. The degradation products of PLA-type materials are glycolic acid and lactic acid, which can participate in the metabolic cycle of carbohydrates in the body. However, the degradation process of larger-sized PLA-type materials (limb bone nails, fixation plates) in the body is prone to form local enrichment of acidic products (glycolic acid and lactic acid), causing immune rejection and bone regeneration disorders. It has been reported that clinical immune rejection reactions mainly include local swelling, sterile abscesses, fistulas and bone resorption. In addition, PLA-type materials also have problems such as lack of osteoconductivity, insufficient mechanical strength, "passive" overall hydrolysis, and "autocatalytic" degradation, which leads to rapid disintegration of materials in the middle and late stages of degradation and large-scale release of acidic products.
[0004] Regenerated silk fibroin materials are mainly made from silkworm cocoons through degumming, dissolution, dialysis, and modification. Soft materials such as sutures and dressing gels made from degummed silk have been widely studied and applied in clinical practice, but there are still many difficulties in the process of making hard silk fibroin materials. At present, the main methods for preparing hard silk fibroin materials include solvent (methanol, etc.) recrystallization method, sol-gel method, and direct thermoforming method.
[0005] However, the above preparation methods also have some problems, which make it difficult to implement industrialization, such as:
[0006] 1. The silk protein materials reported so far based on the methanol recrystallization method have a large number of bubbles (>50%) remaining inside, and the mechanical properties and process stability are difficult to guarantee. It is difficult to prepare large-size materials and cannot be used for product development, which seriously limits the application of silk protein materials.
[0007] 2. The general methanol recrystallization method can solve the problems of bubbles and large-scale production after improvement. However, hexafluoroisopropanol is used as a solvent in the process, which is not only expensive but also harmful to the human body and requires high removal. The inducer methanol has the same problem except for its low cost.
[0008] 3. Direct hot pressing can also produce hard materials of specific shapes, but the requirements for hot pressing equipment and raw materials are too high, and large-scale production is difficult.
[0009] 4. The silk protein hard material obtained by the natural drying method of hydrogel needs to be naturally dried with the help of other reinforcement methods to achieve sufficient mechanical strength, such as UV / riboflavin system, HRP / H2O2 system, chitin / chitosan interpenetrating network, etc. These systems will inevitably require more thorough mixing, but silk protein will produce a large number of bubbles during mixing due to its surfactant-like properties, especially when preparing large industrial samples, the bubbles will be more difficult to escape. If the bubbles cannot be fully removed and remain in the gel system, it will seriously affect the performance of the final hard material, especially the mechanical properties.
[0010] At present, there is no effective solution to the problems existing in the relevant technologies, such as a large number of bubbles remaining inside the silk protein hard materials prepared by methanol recrystallization method and hydrogel natural drying method, high production cost of Silk Science's improved methanol recrystallization method, and difficulty in large-scale production of direct hot pressing molding method. Summary of the invention
[0011] The purpose of the present application is to provide a silk fibroin hard material, a preparation method and an application thereof in view of the deficiencies in the prior art, so as to at least solve the problems existing in the related art, such as a large number of bubbles remaining inside the silk fibroin hard material prepared by the methanol recrystallization method and the hydrogel natural drying method, the high production cost of the improved methanol recrystallization method of Silk Science, and the difficulty of large-scale production by the direct hot pressing molding method.
[0012] To achieve the above purpose, the technical solution adopted by this application is:
[0013] In a first aspect, the present invention provides a method for preparing a silk fibroin hard material, comprising:
[0014] The solution containing the regenerated silk fibroin is subjected to a bubble removal treatment to obtain a high-purity silk fibroin solution or a silk fibroin / gelatin composite solution;
[0015] The high-purity silk fibroin solution or the silk fibroin / gelatin composite solution is subjected to gel treatment to obtain a silk fibroin hard material.
[0016] In some of the embodiments, it also includes:
[0017] The regenerated silk fibroin solution is subjected to a bubble removal treatment to remove bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution;
[0018] The high-purity silk fibroin solution is subjected to gel treatment to obtain a silk fibroin hard material.
[0019] In some of the embodiments, it also includes:
[0020] mixing the regenerated silk fibroin solution with the gelatin solution to obtain a silk fibroin composite solution;
[0021] The silk fibroin composite solution is subjected to a bubble removal treatment to remove bubbles inside the silk fibroin composite solution, and a silk fibroin / gelatin composite solution is obtained;
[0022] The silk fibroin / gelatin composite solution is subjected to gel treatment to obtain a silk fibroin hard material.
[0023] In some embodiments, the method for preparing the regenerated silk fibroin solution comprises:
[0024] Cut the silk cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming, and obtain silk;
[0025] The silk is repeatedly washed with deionized water and dried to obtain silk fibers;
[0026] Putting silk fibers into lithium bromide solution to dissolve, and filtering to obtain silk fibroin stock solution;
[0027] The silk fibroin stock solution is dialyzed and desalted to obtain a silk fibroin solution;
[0028] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol to obtain a regenerated silk fibroin solution.
[0029] In some embodiments, mixing the regenerated silk fibroin solution with the gelatin solution to obtain the silk fibroin composite solution comprises:
[0030] Adding horseradish peroxidase and hydrogen peroxide solution to the regenerated silk fibroin solution to obtain a silk fibroin composite solution;
[0031] The silk fibroin composite solution is mechanically shaken to make the silk fibroin composite solution evenly mixed.
[0032] In some embodiments, mixing the regenerated silk fibroin solution with the gelatin solution to obtain the silk fibroin composite solution comprises:
[0033] The regenerated silk fibroin solution is mixed with the gelatin solution, and a hydrogen peroxide aqueous solution, a transglutaminase, and a horseradish peroxidase are added in sequence to obtain a silk fibroin composite solution;
[0034] The silk fibroin composite solution is mechanically shaken to make the silk fibroin composite solution evenly mixed.
[0035] In some embodiments, the step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises:
[0036] Placing the silk fibroin complex solution in a centrifuge tube;
[0037] The centrifuge tube is placed in a centrifuge for centrifugation to remove bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution.
[0038] In some embodiments, the step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises:
[0039] advecting the silk fibroin composite solution into the mold;
[0040] The mold is placed in an ultrasonic machine for ultrasonic treatment to remove bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution.
[0041] In some embodiments, the step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises:
[0042] advecting the silk fibroin composite solution into the mold;
[0043] A heavy object is placed on the panel of the mold to squeeze the silk fibroin composite solution in the mold to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution.
[0044] In some embodiments, the step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises:
[0045] The silk fibroin composite solution is directly gelled in an extrusion die;
[0046] The mold is placed in a vacuum environment to remove bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution.
[0047] In some embodiments, the step of treating the silk fibroin composite solution to remove bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution comprises:
[0048] advecting the silk fibroin composite solution into the mold;
[0049] placing the mold in a low-temperature environment to freeze the silk fibroin composite solution and obtain a composite solution frozen block;
[0050] dissolving the composite solution block to obtain a silk fibroin composite solution;
[0051] Repeat the above steps 1-2 times to remove the bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution.
[0052] In some embodiments, the step of subjecting the silk fibroin / gel composite solution to gel treatment to obtain a silk fibroin hard material comprises:
[0053] The silk fibroin / gel composite solution is subjected to water bath gelation to obtain a gel block;
[0054] The gel block is immersed in a methanol solution or an ethanol solution to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0055] The silk fibroin hard material is taken out from the methanol solution or the ethanol solution and freeze-dried.
[0056] In a second aspect, the present invention provides a silk fibroin hard material, comprising:
[0057] The product is prepared by the preparation method described in the first aspect.
[0058] In a third aspect, the present invention provides an internal fixation system, including bone screws and / or bone plates;
[0059] The bone nail and / or bone plate is made of the silk fibroin hard material according to claim 8;
[0060] The bone nail and / or bone plate are obtained by the following method: shaping the silk fibroin hard material into a columnar or block-shaped embryo, and processing it with a lathe to obtain the bone nail and / or bone plate;
[0061] The structural strength of the bone screw and / or bone plate is 15-150 MPa in a dry state and 5-50 MPa in a wet state.
[0062] In a fourth aspect, the present invention provides an application of a silk fibroin hard material in the preparation of an internal fixation system, which is applied to trauma orthopedics and plastic surgery (craniofacial). The silk fibroin hard material is prepared by the preparation method described in the first aspect or the silk fibroin hard material described in the second aspect or the internal fixation system described in the third aspect.
[0063] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:
[0064] 1. The raw silk protein used in the present invention is abundant in output, low in price and is a raw material for medical products certified by the U.S. Food and Drug Administration, and has good biocompatibility, biological function and biodegradability.
[0065] 2. Through the delicate degumming, washing, dissolving, dialysis and concentration steps, as well as the centrifugal removal of bubbles, the prepared silk fibroin solution has extremely high purity; high-purity silk fibroin materials are particularly important in biomedicine, tissue engineering and advanced material applications because they can reduce immune responses or adverse effects caused by impurities.
[0066] 3. After gelation and induced crystallization treatment, the silk fibroin hard material exhibits excellent mechanical properties, such as higher strength and toughness; these performance improvements are due to the stable cross-linking and ordered crystalline structure formed between silk fibroin molecules, which enables it to withstand greater stress and deformation without breaking easily.
[0067] 4. As a natural polymer material, silk fibroin has excellent biocompatibility. The use of toxic solvents and additives is avoided during the preparation process, further ensuring the biosafety of the material; this makes silk fibroin hard materials have broad application prospects in the biomedical field, such as drug carriers, tissue repair and regenerative medicine.
[0068] 5. By adjusting the parameters in the preparation process, such as water bath temperature, time, immersion solvent type and time, etc., the structure and properties of silk fibroin hard materials can be precisely controlled; this processability enables the material to meet the specific needs of different application scenarios.
[0069] 6. Most of the solvents and materials used in the entire preparation process are recyclable or biodegradable, with little impact on the environment; in addition, the preparation process is relatively simple and the cost is controllable, which is conducive to large-scale industrial production.
[0070] 7. Silk fibroin hard materials not only have excellent physical and chemical properties, but can also be given more functional properties such as antibacterial, conductive, photosensitivity, etc. through further chemical modification or composite modification, thereby broadening its application range. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0072] Figure 1 is a flow chart (I) of a preparation method according to an embodiment of the present application;
[0073] Figure 2 is a flow chart (II) of the preparation method according to an embodiment of the present application;
[0074] Figure 3 is a flow chart (III) of the preparation method according to an embodiment of the present application;
[0075] Figure 4 is a flow chart (IV) of the preparation method according to an embodiment of the present application;
[0076] Figure 5 is a flow chart of the preparation method according to an embodiment of the present application (V);
[0077] Figure 6 is a flow chart (six) of the preparation method according to an embodiment of the present application;
[0078] Figure 7 is a flow chart of the preparation method according to an embodiment of the present application (VII);
[0079] Figure 8 is a flow chart of the preparation method according to an embodiment of the present application (eight);
[0080] Fig. 9 is a flow chart (IX) of the preparation method according to an embodiment of the present application;
[0081] Fig.10 is a flow chart of a preparation method according to an embodiment of the present application (X);
[0082] Fig.11 is a flow chart of a preparation method according to an embodiment of the present application (XI);
[0083] Fig.12 To adopt Figures 1 to 11 Schematic diagram of a sample prepared by the preparation method (a);
[0084] Fig.13 To adopt Figures 1 to 11 Schematic diagram of the sample prepared by the preparation method (II);
[0085] Fig.14 for Fig.12 , Fig.13Schematic diagram of the test results according to the test method for 4.6 mechanical strength in China's national industry recommended standard YY / T 1558.3. DETAILED DESCRIPTION
[0086] The raw materials of the silk fibroin / gelatin composite material provided by the present invention are all natural biological materials. As a natural biological protein material, silk fibroin has the characteristics of good biocompatibility, easy to obtain, good swelling and natural antibacterial properties. However, due to the slow degradation rate of pure silk protein materials and the lack of bioactive peptides compared with other proteins such as collagen and gelatin, it has a weaker promotion of the biological functions of cells. Pure gelatin is susceptible to thermal denaturation and water absorption expansion. The present invention utilizes the characteristics of silk fibroin rich in tyrosine and gelatin rich in tyrosine, glutamine and lysine, and uses horseradish peroxidase and hydrogen peroxide to oxidize the tyrosine therein to form double tyrosine cross-linking, and uses microbial glutamyl transaminase to form glutamine-lysine isopeptide bonds in gelatin through acyl transfer reaction, and adds alcohol solvent to induce silk protein to form β-folding and ammonium sulfate solution to strengthen gelatin side chain modification. The multi-strategy combined to strengthen the stability and mechanical properties of the silk protein gelatin composite material and give it good biological functions.
[0087] The silk fibroin / gelatin composite material provided by the present invention is a medical biopolymer material, which can be easily processed into absorbable bone nails (or degradable screws). When used in clinical surgery, it can be used in conjunction with traditional orthopedic internal fixation implantation instruments, such as bone drills, tapping, depth finders, etc., to perform internal fixation implantation.
[0088] In order to evaluate the feasibility of processing silk fibroin / gelatin composite materials into absorbable screws, polylactic-co-glycolic acid (PLGA) and regenerated silk protein (RSF) were used as comparative materials in the examples. PLGA is a degradable functional polymer organic compound formed by random polymerization of two monomers, lactic acid and glycolic acid, with good biocompatibility, non-toxicity, good capsule and film-forming properties, and is widely used in pharmaceutical, medical engineering materials and modern industrial fields. Regenerated silk protein, also known as regenerated silk fibroin, is a natural polymer material with a wide range of sources and low prices, and has the advantages of good biocompatibility, degradability and low inflammatory response. Compared with other similar natural polymers, RSF has better biocompatibility and more significant effects on fracture healing. However, although RSF scaffold materials have shown good application prospects in bone tissue engineering, there are still certain defects in their application in clinical treatment, such as unsatisfactory mechanical properties of the scaffold and weak bone induction ability. In order to make RSF suitable for the needs of bone tissue engineering, inorganic reinforcing fillers are usually added therein to construct a composite material.
[0089] Studies have shown that the double shear strength of the silk fibroin / gelatin composite material of the present invention is higher than that of PLGA and regenerated silk fibroin (RSF) in both dry and wet states, that is, the mechanical properties are better.
[0090] The pull-out strength of the silk fibroin / gelatin composite material used in the present invention has no significant difference from that of PLGA and regenerated silk protein (RSF) in either dry or wet state, which can meet the mechanical requirements of clinical surgical operations such as internal fixation of clavicle fractures and mandibular fractures.
[0091] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0092] In the embodiments of the present invention, if there is no specific description on the experimental operation temperature, the temperature generally refers to room temperature.
[0093] This article involves the addition amount, content and concentration of various substances, and the percentages mentioned therein, unless otherwise specified, are all percentages by weight.
[0094] Unless otherwise specified, the "solution" mentioned in this article refers to aqueous solution.
[0095] Example 1
[0096] An exemplary embodiment of the present invention is as follows Figure 1 As shown, a method for preparing a silk fibroin hard material is applied to a high-purity silk fibroin material, comprising:
[0097] Step S110, performing a bubble removal treatment on the regenerated silk fibroin solution to remove bubbles inside the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution;
[0098] Step S120, subjecting the high-purity silk fibroin solution to gel treatment to obtain a silk fibroin hard material.
[0099] like Figure 2 As shown, the method for preparing the regenerated silk fibroin solution in step S110 includes:
[0100] Step S210, cutting the cocoons into pieces, putting them into a sodium carbonate-sodium bicarbonate buffer solution and boiling them for degumming, and obtaining silk;
[0101] Step S220, repeatedly washing the silk with deionized water, and drying to obtain silk fibers;
[0102] Step S230, dissolving the silk fibers in a lithium bromide solution, and filtering to obtain a silk fibroin stock solution;
[0103] Step S240, dialyzing and desalting the silk fibroin stock solution to obtain a silk fibroin solution;
[0104] Step S250, performing reverse dialyzation and concentrating the silk fibroin solution using polyethylene glycol to obtain a regenerated silk fibroin solution.
[0105] It should be noted that the concentration of the sodium carbonate-sodium bicarbonate buffer in step S210 is 0.01M to 0.05M. Preferably, the concentration of the sodium carbonate-sodium bicarbonate buffer is 0.02M.
[0106] It should be noted that in step S220, the drying temperature is 35° C. to 45° C. and the drying time is 20 h to 30 h. Preferably, the drying temperature is 340° C. and the drying time is 24 h.
[0107] It should be noted that the concentration of the lithium bromide solution in step S230 is 8-10 M. Preferably, the concentration of the lithium bromide solution is 9 M.
[0108] It should be noted that the dialysis molecular weight in step S240 is 8000Da to 14000Da. Preferably, the dialysis molecular weight is 10000Da.
[0109] It should be noted that in step S250, the molecular weight of polyethylene glycol is 10000Da to 30000Da, and the concentration of polyethylene glycol is 10% to 20%. Preferably, the molecular weight of polyethylene glycol is 20000Da, and the concentration of polyethylene glycol is 15%.
[0110] It should be noted that the concentration of the regenerated silk fibroin solution in step S250 is 5% to 20%. Preferably, the concentration of the regenerated silk fibroin solution is 10%.
[0111] It should be noted that in step S250, the silk fibroin stock solution is replaced with an aqueous solution 4 to 6 times during the dialysis process. Preferably, the silk fibroin stock solution is replaced with an aqueous solution 5 times during the dialysis process.
[0112] like Figure 3 As shown, step S110 includes:
[0113] Step S310, placing the regenerated silk fibroin solution in a centrifuge tube;
[0114] Step S320: placing the centrifuge tube in a centrifuge for centrifugal treatment to remove bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution.
[0115] It should be noted that the centrifugal speed for treating the silk fibroin composite solution in step S320 is 6000-10000 rpm. Preferably, the centrifugal speed for treating the silk fibroin composite solution is 8000 rpm.
[0116] It should be noted that the centrifugation time for treating the silk fibroin composite solution in step S320 is 5-60 minutes. Preferably, the centrifugation time for treating the silk fibroin composite solution is 30 minutes.
[0117] It should be noted that during the centrifugation of the regenerated silk fibroin solution, centrifugation and gel treatment can be performed simultaneously, that is, gel blocks can be obtained after centrifugation.
[0118] like Figure 4 As shown, further, step S110 also includes:
[0119] Step S410, advecting the regenerated silk fibroin solution into the mold;
[0120] Step S420, placing the mold in an ultrasonic machine for ultrasonic treatment to remove bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution.
[0121] It should be noted that the ultrasonic frequency of treating the high-purity silk fibroin solution in step S420 is 30-100 Hz. Preferably, the ultrasonic frequency of treating the high-purity silk fibroin solution is 70 Hz.
[0122] like Figure 5 As shown, further, step S110 also includes:
[0123] Step S510, advecting the regenerated silk fibroin solution into the mold;
[0124] Step S520: placing a heavy object on the panel of the mold to squeeze the regenerated silk fibroin solution in the mold to remove bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution.
[0125] It should be noted that the extrusion time for treating the high-purity silk fibroin solution in step S520 is 30 to 180 minutes. Preferably, the extrusion time for treating the high-purity silk fibroin solution is 120 minutes.
[0126] like Figure 6 As shown, further, step S110 also includes:
[0127] Step S610, advecting the regenerated silk fibroin solution into the mold;
[0128] Step S620: placing the mold in a vacuum environment to remove bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution.
[0129] It should be noted that the vacuum degree of the high-purity silk fibroin solution in step S620 is 0.1-0.3 MPa and the vacuum time is 30-180 min. Preferably, the vacuum degree of the high-purity silk fibroin solution is 0.2 MPa and the vacuum time is 120 min.
[0130] like Figure 7 As shown, further, step S110 also includes:
[0131] Step S710, advecting the regenerated silk fibroin solution into the mold;
[0132] Step S720, placing the mold in a low-temperature environment, freezing the regenerated silk fibroin solution, and obtaining a solution frozen block;
[0133] Step S730, dissolving the frozen solution block to obtain a regenerated silk fibroin solution;
[0134] Repeat the above steps 1-2 times to remove the bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution.
[0135] It should be noted that the freezing temperature of the high-purity silk fibroin solution in step S720 is -50 to -80°C and the freezing time is 3 to 7 days. Preferably, the freezing temperature of the high-purity silk fibroin solution is -65°C and the freezing time is 5 days.
[0136] It should be noted that step S710 to step S730 are repeated twice to remove bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution.
[0137] It should be noted that the method for removing bubbles in step S110 can also be performed by combining multiple methods, for example:
[0138] 1. The centrifugal treatment method (step S310 to step S320), the ultrasonic treatment method (step S410 to step S420), the constant pressure treatment method (step S510 to step S520), the vacuum treatment method (step S610 to step S620), and the repeated freeze-thaw treatment method (step S710 to step S730) can be combined with each other in pairs (such as ultrasonic treatment + vacuum treatment, extrusion treatment + vacuum treatment, repeated freeze-thaw treatment + centrifugal treatment, etc.).
[0139] 2. Any three of the centrifugal treatment method, ultrasonic treatment method, constant pressure treatment method, vacuum treatment method, and repeated freeze-thaw treatment method can be selected for combined treatment (such as repeated freeze-thaw treatment + ultrasonic treatment + vacuum treatment, repeated freeze-thaw treatment + extrusion treatment + vacuum treatment, etc.).
[0140] like Figure 8 As shown, step S120 includes:
[0141] Step S810, gelling the high-purity silk fibroin solution in a water bath to obtain a gel block;
[0142] Step S820, soaking the gel block in a methanol solution or an ethanol solution to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0143] Step S830: taking out the silk fibroin hard material from the methanol solution or the ethanol solution and freeze-drying it.
[0144] It should be noted that the water bath temperature in step S410 is 30° C. to 40° C., and the water bath time is 6 hours to 24 hours. Preferably, the water bath temperature is 37° C., and the water bath time is 12 hours.
[0145] It should be noted that the soaking time in step S420 is 24 hours to 36 hours. Preferably, the soaking time is 30 hours.
[0146] It should be noted that the drying time in step S430 is 4 to 7 days. Preferably, the drying time is 5 days.
[0147] The present invention has the following advantages:
[0148] 1. The raw silk protein used in the present invention is abundant in output, low in price and is a raw material for medical products certified by the U.S. Food and Drug Administration, and has good biocompatibility, biological function and biodegradability.
[0149] 2. Through the delicate degumming, washing, dissolving, dialysis and concentration steps, as well as the centrifugal removal of bubbles, the prepared silk fibroin solution has extremely high purity; high-purity silk fibroin materials are particularly important in biomedicine, tissue engineering and advanced material applications because they can reduce immune responses or adverse effects caused by impurities.
[0150] 3. After gelation and induced crystallization treatment, the silk fibroin hard material exhibits excellent mechanical properties, such as higher strength and toughness; these performance improvements are due to the stable cross-linking and ordered crystalline structure formed between silk fibroin molecules, which enables it to withstand greater stress and deformation without breaking easily.
[0151] 4. As a natural polymer material, silk fibroin has excellent biocompatibility. The use of toxic solvents and additives is avoided during the preparation process, further ensuring the biosafety of the material; this makes silk fibroin hard materials have broad application prospects in the biomedical field, such as drug carriers, tissue repair and regenerative medicine.
[0152] 5. By adjusting the parameters in the preparation process, such as water bath temperature, time, immersion solvent type and time, etc., the structure and properties of silk fibroin hard materials can be precisely controlled; this processability enables the material to meet the specific needs of different application scenarios.
[0153] 6. Most of the solvents and materials used in the entire preparation process are recyclable or biodegradable, with little impact on the environment; in addition, the preparation process is relatively simple and the cost is controllable, which is conducive to large-scale industrial production.
[0154] 7. Silk fibroin hard materials not only have excellent physical and chemical properties, but can also be given more functional properties such as antibacterial, conductive, photosensitivity, etc. through further chemical modification or composite modification, thereby broadening its application range.
[0155] Example 2
[0156] This embodiment is a variation of the embodiment 1. The main difference between this embodiment and the embodiment 1 is that it further comprises mixing the regenerated silk fibroin solution with the gelatin solution to obtain a silk fibroin composite solution.
[0157] like Fig. 9 As shown, a method for preparing a silk fibroin hard material is applied to a silk fibroin / gelatin composite material, comprising:
[0158] Step S910, mixing the regenerated silk fibroin solution with the gelatin solution to obtain a silk fibroin composite solution;
[0159] Step S920, performing a bubble removal process on the silk fibroin composite solution to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gelatin composite solution;
[0160] Step S930, subjecting the silk fibroin / gelatin composite solution to gel treatment to obtain a silk fibroin hard material.
[0161] It should be noted that the method for preparing the regenerated silk fibroin solution in step S910 is the same as that in Example 1, and will not be described in detail herein.
[0162] It should be noted that in step S910, the concentration of the regenerated silk fibroin solution is 5% to 40%, and the concentration of the gelatin solution is 5% to 40%. Preferably, the concentration of the regenerated silk fibroin solution is 10%, and the concentration of the gelatin solution is 30%.
[0163] like Fig.10 As shown, step S910 includes:
[0164] Step S1010, adding horseradish peroxidase and hydrogen peroxide solution to the regenerated silk fibroin solution to obtain a silk fibroin composite solution;
[0165] Step S1020, mechanically shaking the silk fibroin composite solution to make the silk fibroin composite solution evenly mixed.
[0166] It should be noted that the concentration of the hydrogen peroxide solution in step S1010 is 0.1% to 1.0%, and the dosage of the hydrogen peroxide solution is 500 to 1000 ul. Preferably, the concentration of the hydrogen peroxide solution is 0.5%, and the dosage of the hydrogen peroxide solution is 800 ul.
[0167] It should be noted that the dosage of horseradish peroxidase in step S1010 is 500-1000uL, and the enzyme activity of horseradish peroxidase is 600-1000U / mL. Preferably, the dosage of horseradish peroxidase is 700uL, and the enzyme activity of horseradish peroxidase is 800U / mL.
[0168] It should be noted that the bubble removal process of step S920 is the same as the bubble removal process of step S110 of embodiment 1, and will not be described in detail here. That is, any one of the centrifugal treatment method, ultrasonic treatment method, constant pressure treatment method, vacuum treatment method, and repeated freeze-thaw treatment method, a combination of any two, or a combination of any three.
[0169] The present invention has the following advantages:
[0170] 1. The raw materials silk protein and gelatin used in the present invention are abundant in production, low in price, and are both raw materials for medical products certified by the U.S. Food and Drug Administration, and have good biocompatibility, biological function and biodegradability.
[0171] 2. The horseradish peroxidase and hydrogen peroxide used in the present invention have been commercialized and mass-produced. Among them, low-concentration horseradish peroxidase and hydrogen peroxide have no toxicity and good biocompatibility.
[0172] 3. The silk fibroin / gelatin composite solution prepared by the present invention is easy to mix evenly during the preparation process, and bubbles can be effectively removed by centrifugation to obtain a high-quality composite solution. This good processing performance makes the material more flexible and convenient in the subsequent molding, processing and modification processes.
[0173] 4. The present invention can further promote the cross-linking reaction between silk fibroin and gelatin by introducing cross-linking agents such as horseradish peroxidase and hydrogen peroxide to form a more compact network structure. This cross-linking reaction not only enhances the mechanical properties of the material, but also may give the material more functional properties, such as antibacterial and antioxidant properties.
[0174] 5. The present invention can achieve precise control of the degradation rate of the material by adjusting the ratio of silk fibroin and gelatin and the preparation process. This controllable degradability enables the material to gradually degrade and be absorbed by the human body within a predetermined time according to specific application requirements, avoiding the need for secondary surgery to remove it.
[0175] 6. The preparation method of the present invention is simple and efficient, has no waste or pollution in the whole process, has good repeatability, and has potential value for industrial production.
[0176] Example 3
[0177] This embodiment is a variation of the second embodiment. The main difference between this embodiment and the second embodiment is that step S910 is different.
[0178] like Fig.11 As shown, step S910 includes:
[0179] Step S1110, mixing the regenerated silk fibroin solution with the gelatin solution, and sequentially adding a hydrogen peroxide solution, a transglutaminase, and a horseradish peroxidase to obtain a silk fibroin composite solution;
[0180] Step S1120, mechanically shaking the silk fibroin composite solution to make the silk fibroin composite solution evenly mixed.
[0181] It should be noted that the concentration of the regenerated silk fibroin solution, the concentration of the gelatin solution, the concentration and dosage of the hydrogen peroxide aqueous solution, and the dosage and enzyme activity of the horseradish peroxidase in step S1110 are the same as those in Example 2 and will not be repeated here.
[0182] It should be noted that the dosage of transglutaminase in step S1110 is 10-200ul, and the enzyme activity of transglutaminase is 10-100U / ul. Preferably, the dosage of transglutaminase is 100ul, and the enzyme activity of transglutaminase is 50U / ul.
[0183] The present invention has the following advantages:
[0184] 1. The horseradish peroxidase, hydrogen peroxide and transglutaminase used in the present invention have all been commercialized and mass-produced. Among them, glutaminase is obtained from microorganisms, which is more uniform in stability and rich in yield than the original mammalian source. Low concentrations of horseradish peroxidase and hydrogen peroxide are non-toxic and have good biocompatibility. Experiments and literature have shown that silk protein and gelatin hydrogel cross-linked with horseradish peroxidase and transglutaminase are non-cellular and animal toxic.
[0185] 2. The present invention uses horseradish peroxidase / hydrogen peroxide to induce crosslinking between silk protein itself and silk protein-gelatin, and uses glutamine aminotransferase to modify gelatin side branches, and the obtained hydrogel is immersed in 70% alcohol solution and 15% ammonium sulfate solution in sequence to further induce the formation of small and uniform silk protein β-folds, and strengthen the modification of gelatin side chains. This allows the composite material to have high strength and compressive resistance while achieving stability in simulated in vivo and animal bodies.
[0186] Example 4
[0187] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0188] A method for preparing a silk fibroin hard material, comprising:
[0189] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0190] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0191] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0192] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0193] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0194] Add 700ul of horseradish peroxidase with an enzyme activity of 500U / mL and 700ul of a 0.5% hydrogen peroxide aqueous solution to 20ml of the regenerated silk fibroin solution, and mix them evenly to obtain a silk fibroin composite solution;
[0195] The silk fibroin composite solution is placed in a centrifuge tube, and then placed in a centrifuge for centrifugation at a centrifugal speed of 8000 rpm and a centrifugal time of 30 minutes to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0196] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0197] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0198] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0199] Example 5
[0200] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0201] A method for preparing a silk fibroin hard material, comprising:
[0202] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0203] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0204] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0205] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0206] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0207] Add 700ul of horseradish peroxidase with an enzyme activity of 500U / mL and 700ul of a 0.5% hydrogen peroxide aqueous solution to 20ml of the regenerated silk fibroin solution, and mix them evenly to obtain a silk fibroin composite solution;
[0208] The silk fibroin composite solution is advected into the mold, and the mold is placed in an ultrasonic machine for ultrasonic treatment at an ultrasonic frequency of 50 Hz to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0209] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0210] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0211] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0212] Example 6
[0213] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0214] A method for preparing a silk fibroin hard material, comprising:
[0215] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0216] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0217] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0218] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0219] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0220] Add 700ul of horseradish peroxidase with an enzyme activity of 500U / mL and 700ul of a 0.5% hydrogen peroxide aqueous solution to 20ml of the regenerated silk fibroin solution, and mix them evenly to obtain a silk fibroin composite solution;
[0221] The silk fibroin composite solution is advected into the mold, and a weight is placed on the panel of the mold to squeeze the silk fibroin composite solution in the mold for 120 minutes to remove bubbles inside the silk fibroin composite solution, and obtain a silk fibroin / gel composite solution;
[0222] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0223] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0224] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0225] Example 7
[0226] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0227] A method for preparing a silk fibroin hard material, comprising:
[0228] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0229] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0230] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0231] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0232] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0233] Add 700ul of horseradish peroxidase with an enzyme activity of 500U / mL and 700ul of a 0.5% hydrogen peroxide aqueous solution to 20ml of the regenerated silk fibroin solution, and mix them evenly to obtain a silk fibroin composite solution;
[0234] The silk fibroin composite solution was advected into the mold, and the mold was placed in a vacuum environment with a vacuum degree of 0.2 MPa for 120 minutes to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0235] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0236] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0237] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0238] Example 8
[0239] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0240] A method for preparing a silk fibroin hard material, comprising:
[0241] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0242] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0243] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0244] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0245] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0246] Add 700ul of horseradish peroxidase with an enzyme activity of 500U / mL and 700ul of a 0.5% hydrogen peroxide aqueous solution to 20ml of the regenerated silk fibroin solution, and mix them evenly to obtain a silk fibroin composite solution;
[0247] The silk fibroin composite solution is advected into the mold, and the mold is placed in a low temperature environment of -60°C and frozen for 5 days to freeze the silk fibroin composite solution and obtain a composite solution block, and then the composite solution block is dissolved to obtain a silk fibroin composite solution, and the above steps are repeated twice to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0248] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0249] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0250] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0251] Example 9
[0252] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0253] A method for preparing a silk fibroin hard material, comprising:
[0254] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0255] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0256] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0257] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0258] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0259] A 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution, and a 0.5% hydrogen peroxide solution with a dosage of 700ul, a transglutaminase with a dosage of 100ul and an enzyme activity of 50U / ul, and a horseradish peroxidase with a dosage of 700ul and an enzyme activity of 500U / mL were added in sequence, and mixed evenly to obtain a silk fibroin composite solution;
[0260] The silk fibroin composite solution is placed in a centrifuge tube, and then placed in a centrifuge for centrifugation at a centrifugal speed of 8000 rpm and a centrifugal time of 30 minutes to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0261] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0262] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0263] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0264] Example 10
[0265] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0266] A method for preparing a silk fibroin hard material, comprising:
[0267] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0268] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0269] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0270] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0271] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0272] A 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution, and a 0.5% hydrogen peroxide solution with a dosage of 700ul, a transglutaminase with a dosage of 100ul and an enzyme activity of 50U / ul, and a horseradish peroxidase with a dosage of 700ul and an enzyme activity of 500U / mL were added in sequence, and mixed evenly to obtain a silk fibroin composite solution;
[0273] The silk fibroin composite solution is advected into the mold, and the mold is placed in an ultrasonic machine for ultrasonic treatment at an ultrasonic frequency of 50 Hz to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0274] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0275] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0276] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0277] Embodiment 11
[0278] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0279] A method for preparing a silk fibroin hard material, comprising:
[0280] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0281] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0282] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0283] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0284] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0285] A 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution, and a 0.5% hydrogen peroxide solution with a dosage of 700ul, a transglutaminase with a dosage of 100ul and an enzyme activity of 50U / ul, and a horseradish peroxidase with a dosage of 700ul and an enzyme activity of 500U / mL were added in sequence, and mixed evenly to obtain a silk fibroin composite solution;
[0286] The silk fibroin composite solution is advected into the mold, and a weight is placed on the panel of the mold to squeeze the silk fibroin composite solution in the mold for 120 minutes to remove bubbles inside the silk fibroin composite solution, and obtain a silk fibroin / gel composite solution;
[0287] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0288] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0289] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0290] Example 12
[0291] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0292] A method for preparing a silk fibroin hard material, comprising:
[0293] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0294] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0295] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0296] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0297] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0298] A 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution, and a 0.5% hydrogen peroxide solution with a dosage of 700ul, a transglutaminase with a dosage of 100ul and an enzyme activity of 50U / ul, and a horseradish peroxidase with a dosage of 700ul and an enzyme activity of 500U / mL were added in sequence, and mixed evenly to obtain a silk fibroin composite solution;
[0299] The silk fibroin composite solution was advected into the mold, and the mold was placed in a vacuum environment with a vacuum degree of 0.2 MPa for 120 minutes to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0300] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0301] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0302] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0303] Embodiment 13
[0304] This embodiment relates to a specific implementation of a method for preparing a silk fibroin hard material.
[0305] A method for preparing a silk fibroin hard material, comprising:
[0306] Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk;
[0307] The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers;
[0308] The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution;
[0309] The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution;
[0310] The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%;
[0311] A 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution, and a 0.5% hydrogen peroxide solution with a dosage of 700ul, a transglutaminase with a dosage of 100ul and an enzyme activity of 50U / ul, and a horseradish peroxidase with a dosage of 700ul and an enzyme activity of 500U / mL were added in sequence, and mixed evenly to obtain a silk fibroin composite solution;
[0312] The silk fibroin composite solution is advected into the mold, and the mold is placed in a low temperature environment of -60°C and frozen for 5 days to freeze the silk fibroin composite solution and obtain a composite solution block, and then the composite solution block is dissolved to obtain a silk fibroin composite solution, and the above steps are repeated twice to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution;
[0313] The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block;
[0314] The gel block is placed in a methanol solution or an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material;
[0315] The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
[0316] Embodiment 14
[0317] The samples were prepared according to the methods described in Examples 4 to 13. The states before and after the removal of bubbles were as follows: Fig.12 and Fig.13 As shown. Among them, Fig.12 a is the state where the gel contains bubbles, Fig.12 b is the state of the gel after the bubbles are removed by ultrasonic treatment. Fig.12 c is Fig.12 a The state of bubbles in the rod-shaped blank after solidification, Fig.12 d is Fig.12 b The state where there are no bubbles in the rod-shaped blank after curing. Fig.13 a is the state where the gel contains bubbles in the centrifuge tube, Fig.13 b is the state of the gel after centrifugation to remove bubbles, Fig.13 c is Fig.13 b. The state in which the blank does not contain bubbles after solidification. Other embodiments in this scheme can also achieve the following Fig.12 d and Fig.13 The effect of removing bubbles in c.
[0318] for Fig.12 d and Fig.13 The silk protein solid blank without bubbles in c Fig.12 The silk protein solid blank containing bubbles in c was tested for its compressive properties according to the following methods.
[0319] According to the test method of 4.6 mechanical strength in the Chinese national industry recommended standard YY / T 1558.3, a universal tensile machine is used to customize the metal pressure module and base. The sample is cut into a cylindrical specimen with a diameter of 4mm and a length of 2cm, placed in the center of the metal base, and the pressure module is fixed on it. A universal tensile machine is used to apply a constant speed of pressure to the specimen at a speed of 0.5±0.05mm / min. The test is stopped when the specimen is fractured, and the maximum force value (unit: N) is recorded.
[0320] The results are as follows Fig.14 As shown. The test shows that due to internal defects, the sample block containing bubbles partially collapses when subjected to pressure, and the pressure curve shows a broken line trend. The pressure curve of the sample block without bubbles is a straight line, and the maximum force value is greater than the sample block containing bubbles. After testing, the maximum compressive strength of the sample block after ultrasonic debubbling in Example 5 is: 81.7±2.8Mpa; the maximum compressive strength of the sample with bubbles is: 64.5±4.5Mpa, and the statistical p value is <0.05. The mechanical properties of the sample block after debubbling are significantly better than those of the sample containing bubbles.
[0321] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0322] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a silk fibroin hard material, characterized in that: include: The solution containing the regenerated silk fibroin is subjected to a bubble removal treatment to obtain a high-purity silk fibroin solution or a silk fibroin / gelatin composite solution; The high-purity silk fibroin solution or the silk fibroin / gelatin composite solution is subjected to gel treatment to obtain a silk fibroin hard material.
2. The preparation method according to claim 1, characterized in that: Also includes: The regenerated silk fibroin solution is subjected to a bubble removal treatment to remove bubbles in the regenerated silk fibroin solution and obtain a high-purity silk fibroin solution; The high-purity silk fibroin solution is subjected to gel treatment to obtain a silk fibroin hard material; and / or mixing the regenerated silk fibroin solution with the gelatin solution to obtain a silk fibroin composite solution; The silk fibroin composite solution is subjected to a bubble removal treatment to remove bubbles inside the silk fibroin composite solution, and a silk fibroin / gelatin composite solution is obtained; The silk fibroin / gelatin composite solution is subjected to gel treatment to obtain a silk fibroin hard material.
3. The preparation method according to claim 2, characterized in that: The preparation method of the regenerated silk fibroin solution comprises: Cut the silk cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming, and obtain silk; The silk is repeatedly washed with deionized water and dried to obtain silk fibers; Putting silk fibers into lithium bromide solution to dissolve, and filtering to obtain silk fibroin stock solution; The silk fibroin stock solution is dialyzed and desalted to obtain a silk fibroin solution; Reverse dialyzing and concentrating the silk fibroin solution using polyethylene glycol to obtain a regenerated silk fibroin solution; and / or The step of mixing the regenerated silk fibroin solution with the gelatin solution to obtain a silk fibroin composite solution comprises: Adding horseradish peroxidase and hydrogen peroxide solution to the regenerated silk fibroin solution to obtain a silk fibroin composite solution; Mechanically shaking the silk fibroin composite solution to make the silk fibroin composite solution evenly mixed; and / or The step of mixing the regenerated silk fibroin solution with the gelatin solution to obtain a silk fibroin composite solution comprises: The regenerated silk fibroin solution is mixed with the gelatin solution, and a hydrogen peroxide aqueous solution, a transglutaminase, and a horseradish peroxidase are added in sequence to obtain a silk fibroin composite solution; Mechanically shaking the silk fibroin composite solution to make the silk fibroin composite solution evenly mixed; and / or The step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises: Placing the silk fibroin complex solution in a centrifuge tube; Placing the centrifuge tube in a centrifuge for centrifugation to remove air bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or The step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises: advecting the silk fibroin composite solution into the mold; Placing the mold in an ultrasonic machine for ultrasonic treatment to remove bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or The step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises: advecting the silk fibroin composite solution into the mold; Placing a weight on the panel of the mold to squeeze the silk fibroin composite solution in the mold to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or The step of subjecting the silk fibroin composite solution to a bubble removal process to remove bubbles inside the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises: The silk fibroin composite solution is directly gelled in an extrusion die; Placing the mold in a vacuum environment to remove bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or The step of treating the silk fibroin composite solution to remove bubbles in the silk fibroin composite solution and obtaining a silk fibroin / gel composite solution comprises: advecting the silk fibroin composite solution into the mold; placing the mold in a low-temperature environment to freeze the silk fibroin composite solution and obtain a composite solution frozen block; dissolving the composite solution block to obtain a silk fibroin composite solution; Repeat the above steps 1-2 times to remove the bubbles in the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or The step of subjecting the silk fibroin / gel composite solution to gel treatment to obtain a silk fibroin hard material comprises: The silk fibroin / gel composite solution is subjected to water bath gelation to obtain a gel block; The gel block is immersed in a methanol solution or an ethanol solution to induce crystallization of the gel block to obtain a silk fibroin hard material; The silk fibroin hard material is taken out from the methanol solution or the ethanol solution and freeze-dried.
4. The preparation method according to claim 3, characterized in that: The concentration of the sodium carbonate-sodium bicarbonate buffer is 0.01M to 0.05M; and / or The concentration of the lithium bromide solution is 8 to 10 M; and / or The molecular weight of the polyethylene glycol is 10000Da to 30000Da, and the concentration of the polyethylene glycol is 10% to 20%; and / or The concentration of the regenerated silk fibroin solution is 5% to 20%; and / or The silk is repeatedly washed with deionized water and dried to obtain silk fibers at a drying temperature of 35° C. to 45° C. and a drying time of 20 h to 30 h; and / or The silk fibroin stock solution is dialyzed and desalted to obtain a silk fibroin solution having a dialyzed molecular weight of 8000Da to 14000Da, a dialysis temperature of 20°C to 30°C, and a dialysis time of 48h to 96h; and / or The silk fibroin stock solution is replaced with an aqueous solution 4 to 6 times during the dialysis process.
5. The preparation method according to claim 2, characterized in that: The concentration of the aqueous hydrogen peroxide solution is 0.1% to 1.0%, and the dosage of the aqueous hydrogen peroxide solution is 500 to 1000 ul; The dosage of the transglutaminase is 10 to 200 ul, and the enzyme activity of the transglutaminase is 10 to 100 U / ul; The dosage of the horseradish peroxidase is 500-1000uL, and the enzyme activity of the horseradish peroxidase is 600-1000U / mL.
6. The preparation method according to claim 2, characterized in that: The centrifugal speed for treating the silk fibroin composite solution is 6000-10000 rpm and the centrifugal time is 5-60 min; and / or The ultrasonic frequency of treating the silk fibroin gel solution is 30-100 Hz; and / or The extrusion time for treating the silk fibroin composite solution is 30 to 180 minutes; and / or The silk fibroin composite solution is treated with a vacuum degree of 0.1-0.3 MPa and a vacuum time of 30-180 min; and / or The freezing temperature of the silk fibroin composite solution is -50 to -80°C, and the freezing time is 3 to 7 days; and / or The water bath temperature is 30°C to 40°C, and the water bath time is 6h to 24h; and / or The soaking time is 24h to 36h; and / or The drying time is 4 to 7 days.
7. The preparation method according to any one of claims 1 to 6, characterized in that: include: Cut the cocoons into pieces, put them into a 0.02M sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming to obtain silk; The silk was repeatedly washed with deionized water and dried at 40°C for 24 hours to obtain silk fibers; The silk fibers were dissolved in a 9M lithium bromide solution and filtered to obtain a silk fibroin stock solution; The silk fibroin stock solution was dialyzed and desalted under 10000Da conditions to obtain a silk fibroin solution; The silk fibroin solution was reverse dialyzed and concentrated using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%; Add 700ul of horseradish peroxidase with an enzyme activity of 500U / mL and 700ul of a 0.5% aqueous hydrogen peroxide solution to 20ml of the regenerated silk fibroin solution, and mix them evenly to obtain a silk fibroin composite solution; and / or A 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution, and a 0.5% hydrogen peroxide solution with a dosage of 700ul, a transglutaminase with a dosage of 100ul and an enzyme activity of 50U / ul, and a horseradish peroxidase with a dosage of 700ul and an enzyme activity of 500U / mL were added in sequence, and mixed evenly to obtain a silk fibroin composite solution; Placing the silk fibroin composite solution in a centrifuge tube, and centrifuging it in a centrifuge at a centrifugal speed of 8000 rpm and a centrifugal time of 30 minutes to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or Advecting the silk fibroin composite solution into the mold, and placing the mold in an ultrasonic machine for ultrasonic treatment at an ultrasonic frequency of 50 Hz to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or The silk fibroin composite solution is advected into the mold, and a weight is placed on the panel of the mold to squeeze the silk fibroin composite solution in the mold for 120 minutes to remove bubbles inside the silk fibroin composite solution, and obtain a silk fibroin / gel composite solution; and / or The silk fibroin composite solution was advected into the mold, and the mold was placed in a vacuum environment with a vacuum degree of 0.2 MPa for 120 minutes to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; and / or The silk fibroin composite solution is advected into the mold, and the mold is placed in a low temperature environment of -60°C and frozen for 5 days to freeze the silk fibroin composite solution and obtain a composite solution block, and then the composite solution block is dissolved to obtain a silk fibroin composite solution, and the above steps are repeated twice to remove bubbles inside the silk fibroin composite solution and obtain a silk fibroin / gel composite solution; The silk fibroin / gel composite solution was advected into the mold, and the mold was placed in a water bath at a temperature of 35° C. for 12 hours to gel the silk fibroin / gel composite solution to obtain a gel block; The gel block is placed in a methanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material; and / or The gel block is placed in an ethanol solution and soaked for 30 hours to induce crystallization of the gel block to obtain a silk fibroin hard material; The silk fibroin hard material was taken out from the methanol solution or the ethanol solution and freeze-dried for 5 days.
8. A silk fibroin hard material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. An internal fixation system, characterized in that: including bone screws and / or bone plates; The bone nail and / or bone plate is made of the silk fibroin hard material according to claim 8; The bone nail and / or bone plate are obtained by the following method: shaping the silk fibroin hard material into a columnar or block-shaped embryo, and processing it with a lathe to obtain the bone nail and / or bone plate; The structural strength of the bone screw and / or bone plate is 15-150 MPa in a dry state and 5-50 MPa in a wet state.
10. A use of a silk fibroin hard material in the preparation of an internal fixation system, applied to trauma orthopedics and plastic surgery (craniofacial), characterized in that: The silk fibroin hard material is prepared by the preparation method described in any one of claims 1 to 7 or the silk fibroin hard material described in claim 8 or the internal fixation system described in claim 9.
Citation Information
Cited By
Regenerated silk fibroin material, and preparation method therefor and use thereof
WO2026057053A1